Crosslinked solid electrolyte for lithium ion battery

CN119790519APending Publication Date: 2025-04-08IFP ENERGIES NOUVELLES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062104.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-09-06
Publication Date
2025-04-08

Smart Images

  • Figure CN119790519A_ABST
    Figure CN119790519A_ABST
Patent Text Reader

Abstract

The invention relates to a crosslinkable electrolyte formulation comprising at least:-hydrocarbon molecules containing three to six thiol functions, preferably four; -a bifunctional chain extender in the form of a hydrocarbon chain bearing two C = C double bonds; -a monofunctional single ionic chain terminator containing a C = C double bond and comprising mobile lithium; -a monofunctional polyethylene glycol chain terminator; -a nucleophilic base catalyst, wherein the molar ratio [C = C double bond] / [thiol] is 1. The invention also relates to the preparation and application of the cross-linked solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a cross-linked solid electrolyte for lithium ion batteries based on a thiol-ene reaction. Background Art

[0002] Thiol-ene reactions have applications in many areas, including batteries.

[0003] The thiol-ene (also known as olefin hydrothiolation) reaction is the reaction between thiols and olefins to form thioethers. The reaction was first reported in 1905 but gained importance in the late 1990s and early 2000s due to its feasibility and wide applications, especially for electrolytes.

[0004] Thiols form thiolate anions (RS - ) becomes an excellent nucleophile and reacts via thiol radicals (RS * ) becomes an electrophile. One of the most studied reactions involving thiols is the hydrothiolation of carbon-carbon double bonds (C=C). Depending on the nature of the double bond substituents, i.e., electron donors or acceptors, and the type of catalyst used, the thiol-C=C reaction can proceed by either a free radical mechanism or a nucleophilic mechanism.

[0005] In the case of a nucleophilic mechanism, the reaction used is a Michael addition polymerization (also known as a nucleophilic thiol-ene addition polymerization) with a double bond substituted with an electron withdrawing group, such as (meth)acrylate (a monomer containing a reactive double bond), and a nucleophilic base is used as a catalyst.

[0006] Michael addition polymerization has applications in many fields.

[0007] Li et al., ACS Energy Letters 2018, Vol. 3, pp. 20-27, DOI: 10.1021 / acsenergylett.7b00999, present a single-ion polymer solid electrolyte synthesized by a photoinduced click chemistry reaction of azides with alkynes. It has PEO (poly(ethylene oxide)) repeating units and TFSI (bis{trifluoromethyl(sulfonyl)imide}) counter anions attached to the polymer chain. No crosslinking agent is used, and a viscous liquid polymer is obtained instead of a network (hence the mechanical and physicochemical properties are completely different). Although the migration number is close to 1, the conductivity values ​​described at 90 ° C are about 2×10 -5 S.cm -1 .

[0008] Shen et al., ChemElectroChem 2019, Vol. 6, 4483-4490, DOI: 10.1002 / celc.201901045 proposed a quasi-solid electrolyte in the form of a semi-interpenetrating network formed by a polyacrylate-based monoionic cross-linked polymer and a PEO matrix, thus being independent of the thiol-ene reaction. The counter anion here is sulfonate. Since 5 μl of plasticizer (EC:PC 1:1, volume ratio) was added to the cathode-electrolyte interface during the assembly of the button cell, a conductivity of 1.34 × 10 -5 S.cm -1 The migration number is 0.77.

[0009] Du et al., ACS Appl. Energy Mater, 2020, Vol. 3, 1128-1138, DOI: 10.1021 / acsaem.9b02180, proposed a quasi-solid-state single-ion electrolyte produced by solvent-phase coating of a mixture of PVDF and single-ion polyimide. The counter anion is TFSI, but the obtained electrolyte is a physical network rather than a chemical network, and the synthesis does not involve thiol-ene reactions. Due to its pre-immersion in carbonate solvents during electrochemical characterization, it has a very good conductivity of 1.6×10 at 25°C. -4 S.cm -1 . However, the presence of solvents hinders the industrial development of this type of material, since the goal is to use solid-state electrolytes precisely to avoid the thermal problems associated with solvents in batteries (evaporation, pressure increase, risk of combustion). The migration number is 0.93.

[0010] Zhang et al., Energy Storage Material 2020, Volume 24, Pages 579-587, DOI: 10.1016 / j.ensm.2019.06.029 proposed a quasi-solid-state single-ion electrolyte produced by a mixture of four monomers dissolved in acetonitrile through a photoinduced thiol-ene reaction and deposited on a polypropylene nonwoven fabric. The counter anion is TFSI and the thiol crosslinker is pentaerythritol tetrakis (3-mercaptopropionate). The authors used a solvent in the starting mixture and a support. In addition, it is worth noting that the resulting membrane was immersed in a mixture of ethylene carbonate and dimethylene carbonate before characterization. As a result, an excellent conductivity of 8.4×10 at 25°C was achieved. -4 S.cm -1 is not intrinsic to the material. Furthermore, the proposed network does not contain PEO segments that would facilitate ion conduction in the absence of bulk solvent.

[0011] Patent applications US2016 / 0315348 A1, JR Long, J. Van Humbeck, RP Ameloot, Polymer network single-ion conductors and US2018 / 0166744 A1, R. Long, J. Van Humbeck, JC Axelson, Polymer network single-ion conductors with flexible linkers describe borate anion (C6F4)4B based on - The single-ion polymer network. The nodes are formed by tetrafluorophenylborate anions, and the neutral crosslinkers provide more or less mechanical flexibility depending on their chemical structure. The crosslinker thus also acts as a spacer, and cis-2-butene-1,4-diol is considered the most favorable because it can obtain good structural flexibility. The network formation reaction is carried out in two steps: deprotonation of cis-2-butene-1,4-diol by n-butyllithium, followed by nucleophilic substitution between chloromethane (derived from the lithium chloromethyltetrafluorophenylborate precursor) and the deprotonated cis-2-butene-1,4-diol. The final membrane is obtained by coating with the solvents N,N-dimethylformamide and 2,2'-azobis(2-methylpropionitrile). It is worth noting that the Young's modulus (E = 0.27 GPa) and the ionic conductivity (σ = 8.5×10 at 40°C) are -5 S.cm -1 ) are given for films containing 30% by weight of plasticizer. Therefore, the examples of these patents only relate to gels containing large amounts of propylene carbonate. Summary of the invention

[0012] Surprisingly, the Applicant Company has noticed that in a non-aqueous formulation of a solid electrolyte, crosslinking improves the mechanical properties of the network compared to the use of a homopolymer and that the use of hydrocarbon molecules with 3 to 6 thiol functional groups associated with hydrocarbon molecules containing two C=C double bonds in the presence of a nucleophilic base catalyst, wherein the [olefin] / [thiol] molar ratio in the formulation is substantially stoichiometric, can increase the resistance of the network to chemical degradation. The [olefin] / [thiol] molar ratio is understood to mean the molar ratio of all C=C double bonds to all thiol bonds in the formulation.

[0013] The electrolyte formulation according to the invention can in particular achieve a conductivity (10 -5 Up to 10 -7The crosslinkable electrolyte formulation according to the present invention can obtain a self-supporting chemical network with a transfer number of 1, which can be synthesized in one step through a thiol-ene reaction and does not necessarily require the use of a solvent.

[0014] The present invention relates to a cross-linkable electrolyte formulation comprising at least:

[0015] - hydrocarbon molecules containing three to six thiol functional groups, preferably four;

[0016] - a difunctional chain extender in the form of a hydrocarbon chain with two C=C double bonds;

[0017] - monofunctional monoionic chain terminators containing a C=C double bond and comprising mobile lithium;

[0018] -monofunctional polyethylene glycol chain terminators;

[0019] - a nucleophilic base catalyst,

[0020] The molar ratio of [C=C double bond] / [thiol] is 1.

[0021] The formulation may include a soluble lithium salt or a mixture of soluble lithium salts in the formulation; the amount of lithium salt is 2 wt % to 30 wt % relative to the total formulation weight, preferably, 5 wt % to 15 wt % relative to the total formulation weight.

[0022] The catalyst may be selected from the group consisting of 1,8-diazabicyclo[5.4.0]undec-7-ene, dimethylphenylphosphine, triphenylphosphine or triethylamine, pyridine and dimethylaminopyridine, and is preferably selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, dimethylphenylphosphine, triphenylphosphine or triethylamine, very preferably the catalyst is triethylamine.

[0023] The hydrocarbon molecule containing 3 to 6 thiol functional groups can be selected from the following group: pentaerythritol tetrakis (3-mercaptopropionate), trimethylolpropane tris (3-mercaptopropionate), poly [(mercaptopropyl) methylsiloxane] or (mercaptopropyl) methylsiloxane-co-dimethylsiloxane copolymers having an average functionality greater than or equal to 3, preferably pentaerythritol tetrakis (3-mercaptopropionate).

[0024] The difunctional chain extender may be selected from any oligoethylene glycol unit with two C=C double bonds or any norbornene, vinyl ether, allyl ether, acrylate, methacrylate or olefin unit.

[0025] The bifunctional chain extender may be selected from poly(ethylene glycol) dimethacrylate, PEG diacrylate, PEG diallyl, PEG divinyl.

[0026] The monofunctional monoionic chain terminator is preferably 3-[(trifluoromethane)sulfonamidosulfonyl]propyl lithium methacrylate.

[0027] The polyethylene glycol chain terminator may be selected from the group consisting of poly(ethylene glycol) methyl ether acrylate, poly(ethylene glycol) allyl methyl ether, poly(ethylene glycol) vinyl methyl ether or poly(ethylene glycol) maleimide methyl ether.

[0028] The catalyst may be present in an amount such that the molar ratio of thiol functional groups to catalyst is between 200 and 600.

[0029] The formulation may comprise a second chain extender of the dithiol family, preferably selected from polydimethylsiloxane (PDMS) or polyethylene glycol (PEG) polymers terminated at both ends with mercaptoethyl or mercaptopropyl functional groups.

[0030] The formulation may contain a plasticizer selected from the following compounds: oligoethylene glycol, carbonate, succinonitrile, polar aprotic solvent or aprotic ionic liquid, and the plasticizer accounts for 2% to 30% by weight, preferably 5% to 15% by weight, relative to the weight of the total formulation.

[0031] The present invention also relates to a method for preparing a cross-linked solid electrolyte, wherein:

[0032] a) crosslinking a crosslinkable electrolyte formulation according to any of the preceding variants, in the optional presence of a non-aqueous solvent, by means of a catalyst present in the formulation and by thermal activation, to form a polymer conducting lithium ions,

[0033] b) evaporating the optional solvent present in the polymer to obtain a cross-linked solid electrolyte.

[0034] Heat activation may be performed by heating the formulation at a temperature of 50 to 80°C for a period of 1 to 24 hours, preferably 6 to 12 hours.

[0035] The present invention also relates to the preparation of a cross-linked solid electrolyte in the form of an electrode, wherein in step a), a porous electrode is impregnated with a cross-linkable electrolyte formulation by coating or spraying, and the coated or sprayed formulation is then cross-linked, or active materials and electron permeants are added to the cross-linkable electrolyte formulation in step a) to prepare an electrode ink, which is coated and then cross-linked to obtain a solid electrode.

[0036] The present invention finally relates to the use of a cross-linked electrolyte obtained by cross-linking a formulation according to any of its variants or a cross-linked electrolyte obtained by a method according to any of its variants as a solid electrolyte for an all-solid-state lithium-ion battery or as a component of the positive electrode (cathode electrolyte or cathode electrolyte) or the negative electrode (cathode electrolyte or anode electrolyte) of an electrochemical system.

[0037] List of Figures

[0038] Figure 1 Represents the conductivity (S / cm) as a function of the inverse temperature (1000 / T, T in K) for formulation ABC in the examples (according to the invention) during temperature cycling (down-up-down) between 20°C and 80°C.

[0039] Description of Embodiments DETAILED DESCRIPTION

[0040] The present invention relates to an electrolyte formulation that can be crosslinked by a thiol-ene reaction, wherein at least one monomer comprises an anion with a delocalized charge, such as a TFSI ion, which is covalently bonded and can include a lithium salt to ensure good transport of lithium ions in the electrolyte and the cathode electrolyte. The formulation can obtain a crosslinked electrolyte used as a solid electrolyte for an all-solid-state Li battery or as a component of a positive electrode (cathode electrolyte or cathode electrolyte).

[0041] The novelty of the present invention is the development of an in-situ polymerized and cross-linked single-ion electrolyte, which has the advantage of being initially liquid, forming a chemical network in one step through a thiol-ene reaction, and exhibiting favorable lithium ion transport properties suitable for the application even without a solvent. The cross-linkable formulation according to the present invention is particularly advantageous for the preparation of all-solid-state battery electrodes. Specifically, an electrode prepared according to conventional methods can be used and impregnated with a formulation precursor according to the present invention to form an ion percolation network with a good interface with the active material in situ.

[0042] In the remainder of the description, a "single-ionic" polymer refers to a polymer having a self-doping block or a polymer having monopolar conduction.

[0043] The starting components are all liquids, which are:

[0044] - molecules containing three to six thiol functional groups, preferably four, which act as crosslinkers: the tetrafunctional molecule (A4) may in particular be pentaerythritol tetrakis(3-mercaptopropionate) (preferred), but trivalent thiols (A3) such as trimethylolpropane tris(3-mercaptopropionate) may be used, or poly[(mercaptopropyl)methylsiloxane] or (mercaptopropyl)methylsiloxane-dimethylsiloxane copolymers having an average functionality greater than or equal to 3;

[0045] - a bifunctional chain extender which can be selected from any oligomeric or poly(ethylene glycol) chain with two C=C double bonds (B2): thus, the bifunctional chain extender can be a methacrylate, which is generally more stable than an acrylate, in particular poly(ethylene glycol) dimethacrylate (preferred). More generally, the bifunctional chain extender can be an oligomeric or poly(ethylene glycol) chain with two C=C double bonds selected from the following compounds: PEG diacrylate, PEG dimethacrylate, PEG diallyl, PEG divinyl or any norbornene, vinyl ether, allyl ether, acrylate, methacrylate, maleimide or olefin unit;

[0046] - a monofunctional monoionic chain terminator (B'1) containing a C=C double bond, providing a mobile lithium and a counter anion anchored to the chain, which may specifically be lithium 3-[(trifluoromethane)sulfonamidosulfonyl]propylmethacrylate;

[0047] - a monofunctional polyethylene glycol chain terminator (B″1), which may be selected from the group consisting of poly(ethylene glycol) methyl ether methacrylate, poly(ethylene glycol) methyl ether acrylate, poly(ethylene glycol) allyl methyl ether, poly(ethylene glycol) vinyl methyl ether or poly(ethylene glycol) methyl ether maleimide, and the like.

[0048] It is not necessary to have the same chemical functional groups on the difunctional chain extender (B2) and the monofunctional PEG chain terminator (B1").

[0049] In the crosslinkable electrolyte formulations according to the invention, it is preferred to follow the molar equivalents of thiol and olefin functional groups (stoichiometry equal to 1). The novelty of the formulations according to the invention is that, due to the presence of PEG chain terminators (B"1), the crosslinking density of the network and its mechanical and physicochemical properties are independent of the amount of monoionic chain terminators (B'1). Therefore, the ionic conductivity of the network can be easily adjusted by varying the molar ratio of B1' / B1", without changing the mechanical properties of the electrolyte.

[0050] In one embodiment, a second chain extender of the dithiol family (eg, PDMS or PEG polymers terminated with mercaptoethyl or mercaptopropyl functional groups at both ends) may be added.

[0051] The crosslinking reaction is initiated by a nucleophilic base catalyst commonly used in Michael addition polymerization, also called an initiator. The catalyst may be selected from 1,8 diazabicyclo [5.4.0] undec-7-ene, dimethylphenylphosphine, triphenylphosphine, triethylamine, pyridine or dimethylaminopyridine, and is preferably selected from 1,8 diazabicyclo [5.4.0] undec-7-ene, dimethylphenylphosphine, triphenylphosphine or triethylamine, more preferably the catalyst is triethylamine. Advantageously, a molar ratio of thiol functional group to catalyst is used of between 200 and 600, which corresponds in particular to a molar ratio of tetrafunctional crosslinker to catalyst of about 50 to 150 when the thiol-containing molecule is tetrafunctional (four thiol functional groups).

[0052] Therefore, the crosslinkable electrolyte formulation according to the present invention comprises at least the following components:

[0053] - molecules with three to six thiol functions, for example four thiol functions (pentaerythritol tetrakis(3-mercaptopropionate) in the example), or three or six if a change in the flexibility of the final material is desired,

[0054] - a chain extender with two C=C double bonds (in the embodiment poly(ethylene glycol) dimethacrylate): the chain extender is advantageously selected from any oligoethylene glycol unit with two C=C double bonds or any norbornene, vinyl ether, allyl ether, acrylate, methacrylate, maleimide or olefin unit,

[0055] - a monofunctional monoionic chain terminator containing one C=C double bond, which provides mobile lithium and a counter anion anchored (i.e. covalently bonded) to the chain and can generate side chains to provide mechanical flexibility (lithium 3-[(trifluoromethane)sulfonamidosulfonyl]propylmethacrylate in the example),

[0056] - monofunctional polyethylene glycol chain terminator,

[0057] -Nucleophilic base catalyst (triethylamine in the embodiment):

[0058] o The amount of catalyst used is advantageously about 0.04 molar equivalents, the exact amount of which can be chosen by one skilled in the art.

[0059] In one embodiment of the present invention, the cross-linkable electrolyte formulation comprises:

[0060] - pentaerythritol tetrakis(3-mercaptopropionate) (A4);

[0061] - poly(ethylene glycol) dimethacrylate (B2);

[0062] -3-[(trifluoromethane)sulfonamidesulfonyl]propyllithium methacrylate (B'1),

[0063] - poly(ethylene glycol) methyl ether methacrylate (B"1),

[0064] - triethylamine as catalyst, preferably the molar ratio of tetrafunctional crosslinking agent (A4) to catalyst is between 50 and 150.

[0065] Optionally, a lithium salt soluble in the starting formulation or a mixture of several salts soluble in the starting formulation may be added. The lithium salt(s) soluble in the starting formulation are preferably selected from LiTFSI, LiPF6, LiFSI, LiClO4, LiTDI, very preferably the soluble lithium salt is LiTFSI, or any mixture of several lithium salts soluble in the starting formulation. The exact amount of the soluble lithium salt may be between 2% and 30% by weight of the starting formulation, and preferably between 5% and 15% by weight.

[0066] A plasticizer may be added, which is selected from the following compounds: oligoethylene glycols, alkyl carbonates, succinonitrile, polar aprotic solvents of low volatility or aprotic ionic liquids. The amount of plasticizer may be between 2% and 30% by weight of the starting formulation, and preferably between 5% and 15% by weight.

[0067] The crosslinkable liquid formulation according to the present invention can be formed between two plates, or formed by coating or spraying onto a support, and then crosslinking to form a network is carried out by heating at a temperature between 50° C. and 80° C. for 1 to 24 hours, preferably 6 to 12 hours. The catholyte or anolyte can be formed by impregnating a porous electrode with the liquid formulation (coating or spraying) or by mixing the liquid formulation with an active material to form an ink, optionally in the presence of a solvent, which evaporates after crosslinking.

[0068] In the case where the solid electrolyte is in contact with the positive electrode, the liquid cross-linkable formulation according to the present invention can be coated or sprayed on the positive electrode prepared in advance according to the protocol of a person skilled in the art, so that the liquid formulation wets the pores of the electrode. Finally, cross-linking is achieved after thermal initiation. Preferably, the formulation is coated or sprayed before calendering the electrode, and then cross-linking is performed.

[0069] For example, the formulation according to the present invention can be used to prepare a positive electrode (cathode) ink, specifically by adding an active material (such as a lithiated nickel manganese cobalt mixed oxide or a lithiated iron phosphate) and an electron permeating agent to the formulation. Once this ink is applied and dried, it can form a solid positive electrode.

[0070] Characterization techniques

[0071] The ionic conductivity of an electrolyte is measured in S / cm and characterizes the ability of the electrolyte to transport ions.

[0072] pass Electrochemical impedance spectroscopy in CESH cells measures the ionic conductivity of the electrolyte. The ITS chamber is used for measurements at multiple temperatures. Obtained with a MTZ 35 potentiostat between 30 MHz and 0.1 Hz, around 0 V, with an amplitude of ±10 mV. The conductivity value can be determined by adjusting the curve with an equivalent circuit of the (R1+R2 / / CPE1+CPE2) type, or visually by taking the value of the real part of the impedance Re(Z) at the minimum reached by the curve between the semicircle and the semi-straight line corresponding to the capacitive part on the Nyquist plot.

[0073] The cation migration number (t+) corresponds to the fraction of the total conductivity associated with the cation migration charge and is characterized by impedance spectroscopy measured at 60°C using a Biologic VMP3 potentiostat between 1 MHz and 0.1 MHz, around 0 V, with an amplitude of 10 mV on a sample mounted between two non-blocking electrodes (made of lithium metal). The migration number is obtained by adjusting the equivalent circuit (R1+R2 / / CPE2+R3 / / CPE3+Wd1) and then applying the following formula: t+=R2 / (R Wd1 +R2). This measurement method corresponds to the "Watanabe" method (Solid State Ionics, 28-30 (1988), 911-917).

[0074] Solvent swelling tests and calculation of the soluble fraction are traditional methods to characterize polymer networks in order to indirectly assess their crosslink density and their chemical stability. After approximately 300 mg of a polymer network sample was immersed in a large excess of chloroform (CHCl3) at ambient temperature for 72 hours, the swollen sample was weighed and then dried in vacuo.

[0075] The soluble fraction (ws) was calculated using the following formula:

[0076] ws=1–w d / w0

[0077] where w0 is the initial weight of the sample swollen with the solvent (estimated by linear regression of the weight curve measured at fixed time intervals from 0.5 to 5 min after the sample was removed from the solvent), w d is the weight of the sample after the soluble portion has been extracted and dried.

[0078] The degree of swelling, corresponding to the increase in volume of the network after immersion in the solvent, (1 / q2) is calculated using the following formula:

[0079] 1 / q2=ρ p(q1–1) / ρ s

[0080] Where q1 is the ratio of the weight of the swollen sample to the weight of the dry sample, ρ s is the density of the solvent (for CHCl3, ρ s =1.492g.cm –3 ), ρ p is the density of the polymer network.

[0081] Various techniques can characterize the thermomechanical properties of single-ion polymer networks.

[0082] Differential Scanning Calorimetry (DSC) is a technique for characterizing thermochemical processes, including phase and state changes. Here, it is used to determine the glass transition temperature (T g ).

[0083] Differential Scanning Calorimetry (DSC) experiments were performed using a DSC Q200 (TA Instruments) instrument calibrated with indium standards. Samples (5 to 10 mg) were prepared using hermetically sealed capsules and were heated at 25 ml min –1 The measurement was carried out in a helium flow. The sample was first heated to 120°C at a heating rate of 10°C min – 1 , and then kept at this temperature for 2 minutes. Subsequently, the temperature was increased at 10 °C min – 1 The cooling rate was reduced to –80 °C and then, after 2 min of isothermal heating, the temperature was raised to 10 °C min – 1 The glass transition temperature (T) was measured at the half-height of the transition occurring during the second heating using TA thermal analysis software. g ).

[0084] Thermogravimetric analysis is a technique that can characterize the weight loss curve of a sample under temperature changes. This characterizes chemical changes in the material with temperature changes, such as evaporation or chemical degradation.

[0085] Thermogravimetric analysis (TGA) experiments were performed using a TGA Q500 (TA Instruments) instrument at 20 °C min –1 The temperature was raised and kept at 110 °C for 8 min to avoid weight loss due to the presence of water. –1 Under continuous helium flow, the –1 About 8 mg of the sample was heated from 20°C to 600°C at a rate of .

[0086] Advantages of the invention

[0087] In particular, compared to prepolymerized polymers, the crosslinkable electrolyte formulation according to the invention exhibits the advantage that it is initially liquid, which enables it to obtain good cohesion at the interface with the electrode, in particular due to an easier filling of the pores of the material. The single ion character (t+=1) makes Li + The ions are evenly distributed in the material, which can eliminate the concentration gradient of ions in the material under the action of the electric field (charging and discharging of the battery). + The overvoltage associated with ion diffusion through the material is greatly reduced.

[0088] The controlled crosslinking of a specific monomer mixture and the specific morphology of the three-dimensional network further impart a higher mobility to the chains, thereby improving ion conduction. The performance qualities of the solid electrolyte according to the invention are based in particular on the specific selection of certain monomers that have a high flexibility and are good solvents for lithium ions, and on controlled crosslinking.

[0089] The rheological behavior obtained for the crosslinked electrolyte samples according to the invention corresponds advantageously to that of crosslinked polymers.

[0090] Example:

[0091] Materials and methods:

[0092] For the sake of simplicity in notation, the products that make up the network will be named as follows:

[0093] -Pentaerythritol tetrakis(3-mercaptopropionate): A4

[0094] -Poly(ethylene glycol) dimethacrylate: B2

[0095] -3-[(Trifluoromethane)sulfonamidesulfonyl]propyllithium methacrylate: B'1

[0096] -Poly(ethylene glycol) methyl ether methacrylate: B"1

[0097] -Triethylamine: Et3N

[0098] The molar equivalent of the functional group is 2A4=2B2+2(B'1+B"1).

[0099] The starting liquid mixture was deposited between two glass plates covered with Teflon tape and separated by a 200 μm thick PTFE membrane for ionic conductivity and migration number measurements and a 2 mm thick PTFE membrane for thermomechanical characterization. The device was placed in an oven at 60 ° C for 12 h. The resulting solid samples were dried on a Buchi dryer before characterization.

[0100] Solvent swelling tests and calculation of the soluble fraction are traditional methods for characterizing polymer networks in order to indirectly estimate their crosslinking density and their chemical stability. These tests were performed after immersing about 300 mg of the network in a large excess of chloroform (CHCl3) at ambient temperature for 72 hours. The swollen network was weighed and then dried under vacuum. The insoluble content was calculated using the following formula:

[0101] Ci=(w d / w0)×100

[0102] Where w0 is the initial weight of the sample, w d is the weight of the sample after the soluble portion has been extracted and dried.

[0103] The swelling degree (1 / q2) is calculated using the following formula:

[0104] 1 / q2=ρ p (q1–1) / ρ s

[0105] Where q1 is the ratio of the weight of the swollen sample to the weight of the dry sample, ρ s is the density of the solvent (for CHCl3, ρ s =1.492g.cm –3 ), ρ p is the density of the polymer network (ρ p ≈1).

[0106] The thermomechanical properties of the monoionic polymer networks were characterized by DSC, TGA and DMA to determine the glass transition values, T g , 10% weight loss decomposition temperature T d10 As well as the storage modulus value E' and α transition temperature value T at the rubber platform α .

[0107] Differential Scanning Calorimetry (DSC) experiments were performed using a DSC Q200 (TA Instruments) instrument calibrated with indium standards. Samples (5 to 10 mg) were prepared using hermetically sealed capsules and were heated at 25 ml min –1 The measurement was carried out in a helium flow. The sample was first heated to 120°C at a heating rate of 10°C min –1 , and then kept at this temperature for 2 minutes. Subsequently, the temperature was increased at 10 °C min –1 The cooling rate was reduced to –80 °C and then, after 2 min of isothermal heating, the temperature was raised to 10 °C min – 1 The glass transition temperature (T) was measured at the half-height of the transition occurring during the second heating using TA thermal analysis software. g ).

[0108] Thermogravimetric analysis (TGA) experiments were performed using a TGA Q500 (TA Instruments) instrument at 20 °C min –1 The temperature was raised and kept at 110 °C for 8 min to avoid weight loss due to the presence of water. –1 Under continuous helium flow, the –1 About 8 mg of the sample was heated from 20°C to 600°C at a rate of .

[0109] pass Impedance spectroscopy in CESH cells measures the ionic conductivity of the electrolyte. The ITS chamber is used for measurements at multiple temperatures. Acquired with a MTZ 35 potentiostat between 30 MHz and 0.1 Hz, around 0 V, with an amplitude of 10 mV.

[0110] The migration number of the samples was measured by impedance spectroscopy. The electrolyte was located between two lithium metal electrodes and characterized at 60 °C. The VMP3 potentiostat collects impedance spectra at 0V, 10mV amplitude, 1MHz and 0.1MHz. The impedance spectrum is adjusted by an equivalent circuit, and then the electrolyte and diffusion resistances can be extracted. From these resistances the migration number is calculated.

[0111] Three formulations were tested in order to vary the molar ratios of the four starting components, in particular the amount of lithium in the resulting single ion network (proportional to the weight percentage of B'1), and to test the effect of adding a lithium salt (here LiTFSI) and a plasticizer (here succinonitrile). The catalyst (nucleophilic base initiator) was added last, with a constant molar equivalent (0.04). Table 1 shows the components of samples A to C (in molar equivalents), and the weight % of lithiated chain terminator and the weight % of plasticizer in the starting formulations.

[0112] Table 1

[0113]

[0114] Table 2 shows the results obtained after immersion of the networks in chloroform at ambient temperature (insoluble content Ci and swelling degree S of networks A to C). It is noteworthy that all three formulations lead to materials with good chemical stability, since the insoluble content is greater than 85%. The low swelling values ​​(less than 5) reflect the very good crosslinking of the network.

[0115] Table 2

[0116]

[0117] Table 3 Glass transition temperature T of networks A to C g and the decomposition temperature T of 10% of the initial weight d10 ) shows the results obtained from DSC and TGA analysis. It is noteworthy that the glass transition temperature is low (not exceeding -15°C), which reflects sufficient segment mobility for lithium ion conduction in the operating temperature range of the battery. The decomposition temperature of 10% of the initial weight of the three formulations tested is higher than 280°C, which fully meets the expected application areas.

[0118] Table 3

[0119]

[0120] Figure 1 The conductivity measurements of the networks obtained from the three tested formulations A, B, and C are shown. It is observed that when the weight fraction of the monoionic chain terminator increases from 26 wt % to 32 wt %, the conductivity of the final network also increases (6.7×10-60°C, 6.7×10-70°C, 6.7×10-80°C, and 6.7×10-90°C, respectively) due to the provision of mobile lithium ions to the system. -6 and 9.5×10 -6 S cm -1 In addition, if a small amount of lithium salt and plasticizer are added to the starting formulation, the conductivity is further improved (1.4×10 - 5 S cm -1 ).

[0121] Formulations A and B obtained transference numbers equal to 1, which is characteristic of a single ion system. Network C has a transference number less than 1 due to the presence of the lithium salt.

Claims

1. A cross-linkable electrolyte formulation comprising at least: - hydrocarbon molecules containing three to six thiol functional groups, preferably four; - a difunctional chain extender in the form of a hydrocarbon chain with two C=C double bonds; - monofunctional monoionic chain terminators containing a C=C double bond and comprising mobile lithium; -monofunctional polyethylene glycol chain terminators; - a nucleophilic base catalyst, - wherein the molar ratio [C═C double bond] / [thiol] is 1.

2. The crosslinkable electrolyte formulation according to claim 1, wherein the formulation comprises a soluble lithium salt or a mixture of soluble lithium salts in the formulation, and wherein the amount of lithium salt is 2 wt. % to 30 wt. % relative to the total formulation weight, preferably 5 wt. % to 15 wt. % relative to the total formulation weight.

3. A crosslinkable electrolyte formulation as claimed in any one of the preceding claims, wherein the catalyst is selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, dimethylphenylphosphine, triphenylphosphine or triethylamine, pyridine and dimethylaminopyridine, and is preferably selected from 1,8-diazabicyclo[5.4.0]undec-7-ene, dimethylphenylphosphine, triphenylphosphine or triethylamine, very preferably triethylamine.

4. A crosslinkable electrolyte formulation as claimed in any one of the preceding claims, wherein the hydrocarbon molecule containing 3 to 6 thiol functional groups is selected from the group consisting of pentaerythritol tetrakis (3-mercaptopropionate), trimethylolpropane tris (3-mercaptopropionate), poly [(mercaptopropyl) methylsiloxane] or a (mercaptopropyl) methylsiloxane-co-dimethylsiloxane copolymer having an average functionality greater than or equal to 3, preferably pentaerythritol tetrakis (3-mercaptopropionate).

5. A crosslinkable electrolyte formulation as claimed in any one of the preceding claims, wherein the difunctional chain extender is selected from any oligoethylene glycol unit with two C=C double bonds or any norbornene, vinyl ether, allyl ether, acrylate, methacrylate or olefin unit.

6. The crosslinkable electrolyte formulation of claim 5, wherein the difunctional chain extender is selected from poly(ethylene glycol) dimethacrylate, PEG diacrylate, PEG diallyl, PEG divinyl.

7. The crosslinkable electrolyte formulation of any one of the preceding claims, wherein the monofunctional monoionic chain terminator is lithium 3-[(trifluoromethane)sulfonamidosulfonyl]propylmethacrylate.

8. The crosslinkable electrolyte formulation of any one of the preceding claims, wherein the polyethylene glycol chain terminator is selected from the group consisting of poly(ethylene glycol) methyl ether acrylate, poly(ethylene glycol) allyl methyl ether, poly(ethylene glycol) vinyl methyl ether or poly(ethylene glycol) maleimide methyl ether.

9. The crosslinkable electrolyte formulation according to any one of the preceding claims, comprising a catalyst in an amount such that the molar ratio of thiol functional groups to catalyst is between 200 and 600.

10. A crosslinkable electrolyte formulation as claimed in any one of the preceding claims, comprising a second chain extender of the dithiol family, preferably selected from polydimethylsiloxane (PDMS) or polyethylene glycol (PEG) polymers terminated at both ends with mercaptoethyl or mercaptopropyl functional groups.

11. A crosslinkable electrolyte formulation as claimed in any one of the preceding claims, comprising a plasticizer selected from the following compounds: oligoethylene glycols, carbonates, succinonitrile, polar aprotic solvents or aprotic ionic liquids, the plasticizer accounting for 2% to 30% by weight, preferably 5% to 15% by weight, relative to the total formulation weight.

12. A method for preparing a cross-linked solid electrolyte, wherein: a) crosslinking the crosslinkable electrolyte formulation as claimed in any one of the preceding claims, in the optional presence of a non-aqueous solvent, by means of a catalyst present in the formulation and by thermal activation, to form a polymer conducting lithium ions, b) evaporating the optional solvent present in the polymer to obtain a cross-linked solid electrolyte.

13. The method for preparing a cross-linked solid electrolyte according to claim 12, wherein the thermal activation is performed by heating the formulation at a temperature of 50°C to 80°C for a period of 1 to 24 hours, preferably 6 to 12 hours.

14. A method for preparing a cross-linked solid electrolyte in the form of an electrode as described in claim 12 or 13, wherein in step a), the porous electrode is impregnated with a cross-linkable electrolyte formulation by coating or spraying, and the coated or sprayed formulation is then cross-linked, or active materials and electron permeants are added to the cross-linkable electrolyte formulation in step a) to prepare an electrode ink, which is coated and then cross-linked to obtain a solid electrode.

15. Use of a cross-linked electrolyte obtained by cross-linking the formulation as described in any one of claims 1 to 11 or a cross-linked electrolyte obtained by the method as described in any one of claims 12 to 14 as a solid electrolyte for an all-solid-state lithium-ion battery or as a component of the positive electrode (positive electrode electrolyte or negative electrode electrolyte) or the negative electrode (negative electrode electrolyte or anolyte) of an electrochemical system.

Citation Information

Patent Citations

  • Polymer network single ion conductors

    US20160315348A1

  • Polymer network single-ion conductors with flexible linker

    US20180166744A1